Probiotic therapy as a novel approach in the prevention and treatment of gingivitis. A review - Longo, Mariellen; Ramos, Tatiane Caroline de Souza; Nunes, Camilla Magnoni Moretto; Santamaria, Mauro Pedrine; Neves Jardini, Maria Aparecida (Brazilian Dental Science, 2018)
Gingivitis is caused by a mixture of Gram-positive and Gram-negative species and is characterized by inflammatory exudate in the marginal region. Probiotics have been introduced in the prevention and treatment of periodontal diseases and represent an innovative approach to maintaining oral health using beneficial bacteria when administered in adequate amounts. The mechanism of action of probiotics in the oral cavity is not fully understood but is commonly explained by a combination of local and systemic immunomodulation. The results of the studies suggest that probiotics may be useful in the prevention and treatment of gingivitis, but their effectiveness is still very questionable. Thus, more in vivo research is needed through randomized controlled studies evaluating the main periodontal clinical parameters, levels of inflammatory mediators and microbiological analyzes, especially to elucidate some still unknown mechanisms of action and to ensure the use of probiotics as an effective therapy in the prevention and treatment of gingivitis. Keywords Gingivitis; Probiotics; Periodontal treatment.